2019
DOI: 10.3390/medicina55090545
|View full text |Cite
|
Sign up to set email alerts
|

Can Visceral Adiposity Index Serve as a Simple Tool for Identifying Individuals with Insulin Resistance in Daily Clinical Practice?

Abstract: Background and objectives: The visceral adiposity index (VAI), estimating visceral adiposity dysfunction through a simple formula, could serve as a useful tool for identifying individuals at higher cardiometabolic risk. Its relationship with insulin resistance (IR), assessed using the homeostasis model assessment of IR (HOMA-IR), and metabolic syndrome (MetS) components remains unclear. The study aimed to investigate the association of VAI with both HOMA-IR and MetS. Materials and Methods: After undergoing ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Decreases in serum HDL and increases in triglycerides were reported to be linked with inflammatory status and mediators (38). Likewise, VAI was reported to be strongly correlated with insulin resistance estimated by HOMA-IR and metabolic syndrome (39,40). Furthermore, among the most commonly used adiposity assessment indices, VAI has the strongest correlation with the most well-known adipocytokines in diabetic patients (41) and non-diabetic (42).…”
Section: Discussionmentioning
confidence: 99%
“…Decreases in serum HDL and increases in triglycerides were reported to be linked with inflammatory status and mediators (38). Likewise, VAI was reported to be strongly correlated with insulin resistance estimated by HOMA-IR and metabolic syndrome (39,40). Furthermore, among the most commonly used adiposity assessment indices, VAI has the strongest correlation with the most well-known adipocytokines in diabetic patients (41) and non-diabetic (42).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive visceral adipose tissue (VAT) accumulation has been proved to be an essential trigger of metabolic diseases and is strongly associated with an elevated risk of CVD (Liu et al, 2016;Štěpánek et al, 2019). Postmenopausal women with visceral obesity should be screened due to their heightened risk.…”
Section: Discussionmentioning
confidence: 99%
“…The VAI cut-off point was 4.24 in predicting insulin resistance. In a study by Stepanek et al on 783 participants, they found the VAI cut-off point to be 2.37 in predicting MetS and insulin resistance (Those with HOMA: 3.8 and above were considered to have insulin resistance) [20]. In a study conducted on overweight and obese patients, the VAI cut-off points for predicting insulin resistance were found to be 2.3 [9].…”
Section: Discussionmentioning
confidence: 99%